2011
DOI: 10.32468/dtseru.146
|View full text |Cite
|
Sign up to set email alerts
|

Raizales y continentales: un análisis del mercado laboral en la isla de San Andrés

Abstract: La serie Documentos de Trabajo Sobre Economía Regional es una publicación del Banco de la República -Sucursal Cartagena. Los trabajos son de carácter provisional, las opiniones y posibles errores son de responsabilidad exclusiva de los autores y no comprometen al Banco de la República ni a su Junta Directiva. es economista del Banco de la República -Cartagena. Los comentarios y sugerencias a esta versión del documento pueden ser enviados a los correos electrónicos jyabruve@banrep.gov.co o javieryabrudy@hotmail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Several have suggested that diversity in management reduces barriers to career advancement (Dalvit et al 2021;Kunze and Miller 2017;Mateos de Cabo et al 2011;Matsa and Miller 2011). And others have referred to equality as a method to reduce the GWG (Bell 2005;Bertrand et al 2019;Cardoso and Winter-Ebmer 2010;Cohen and Huffman 2007;Flabbi et al 2019;Theodoropoulos et al 2022;Hensvik 2014;Hirsch 2013;Vega et al 2016). However, the results were quite varied in terms of significance and the size of the specific group of women affected.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several have suggested that diversity in management reduces barriers to career advancement (Dalvit et al 2021;Kunze and Miller 2017;Mateos de Cabo et al 2011;Matsa and Miller 2011). And others have referred to equality as a method to reduce the GWG (Bell 2005;Bertrand et al 2019;Cardoso and Winter-Ebmer 2010;Cohen and Huffman 2007;Flabbi et al 2019;Theodoropoulos et al 2022;Hensvik 2014;Hirsch 2013;Vega et al 2016). However, the results were quite varied in terms of significance and the size of the specific group of women affected.…”
Section: Literature Reviewmentioning
confidence: 99%